Populações de Hypsiboas albopunctatus (Anura, Hylidae) de ambientes urbanos e rurais diferem em relação às vocalizações, morfometria e aos tamanhos populacionais? - Amaral, Ivan Borel (2009)
In recent years, population declines of amphibians have been observed in different parts of the world. The process of fragmentation and destruction of habitats is considered the most threat to this diversity. Urbanization reduces species richness at assemblage of amphibian reproduction. Due to amphibians require a modest area for survival, some species can thrive in urban fragments. But small population sizes and isolation can cause the loss of genetic diversity and the extinction local. The advertisement calls are the most common vocalizations in anurans that primarily have the function to attract females and secondarily, serve to mediate aggressive interactions between males. For many species, individual reproductive success is directly proportional to the effort put in the corner. The variation between populations may be related to local adaptation, resource availability and reduced gene flow. This study aimed to test the following hypotheses: ( 1 ) Due to the effects of fragmentation and habitat destruction and urbanization , population sizes of Hypsiboas albopunctatus urban parks are smaller than the population size of rural populations , (2 ) There are differences morphometric H. albopunctatus between rural and urban environments , and ( 3 ) Due to the change of social structure as a function of fragmentation and influence of urban noise , there are differences in vocalizations of H. albopunctatus between rural and urban environments . The H. albopunctatus populations of urban and rural environments differ in population size , the body size and characteristics of the advertisement call. Urban populations were smaller than those of the rural environment. The results showed that populations are lower in smaller and changed urban fragments . Urban populations had a lower repetition rate of notes compared to rural environment . This fact may be related mainly to reduced population sizes and consequent behavioral change and structure of choirs of urban environments. It is unreasonable to reject the hypothesis that the sounds of car engines may influence the acoustic parameters of the corners of H. albopunctatus in urban environment. The population of H. albopunctatus Zoo vocalised in higher frequency bands and acoustic variable that is inversely related to body size of individuals as in other anurans. The population of this fragment was the one that differed from all others in both acoustic as morphometric characteristics. These results support the hypothesis that there are differences in the characteristics of the advertisement calls of Hypsiboas albopunctatus between rural and urban environments. The population of P. M. Jardim Botânico was the most distanced itself from the other urban populations in both acoustic and morphometric characteristics as the population size. This population was the most resembled the population characteristics of the rural environment. A same species of amphibian populations may have considerably differences in population structure, morphological and behavioral characteristics due to the fact that some are under the influence of the urban environment and other rural environment. The planning for the conservation of such populations requires more refined analysis that takes into account the aspects of ecological, behavioral and adaptive responses of this species in their specific environment.